ANALISIS PROYEKSI KEBUTUHAN RUANG PADA KELURAHAN LASOANI DI KECAMATAN MANTIKULORE PALU - Deltri Dikwardi Eisenring; Hilmansyah, Teguh; Amin, Moh; Renaldi, Renaldi (Plano Madani : Jurnal Perencanaan Wilayah dan Kota, 2024)
Facilities and infrastructure in a region are crucial aspects of human life. With the presence of facilities and infrastructure in an area, individuals can smoothly carry out their daily activities. Mantikulore district is one of the districts that emerged from East Palu the main district, and one of its sub-districts is Lasoani sub-district. Therefore, an analysis is necessary regarding the projected space needs in Lasoani sub-district utilizing an information system encompasses data and maps of facilities and infrastructure designed for the process of collecting and storing object data. Based on the description, the researchers are keen on analyzing the analysis of space requirements in the Lasoani sub-district of Mantikulore district. The method employed during the analysis stage involves interpreting field-collected data into a map illustrating the distribution of infrastructure, utilizing satellite data and drones. Additionally, an analysis of space requirements will be conducted, encompassing population projections and facility projections for the next 20 years, from 2022 to 2042, in Lasoani sub-district. The calculation of projected space requirements adheres to SNI standards 03-1733-2004: Procedures for Planning Housing Environments in Urban Areas, planning needs for Environmental Infrastructure and Facilities.